ETHICAL FRAMEWORK FOR ARTIFICIAL INTELLIGENCE IN PROFESSIONAL PRACTICES OF HIGHER EDUCATION LECTURERS: A SYSTEMATIC REVIEW - Khairul Hamimah Mohd Jodi; Muhammad Zulfadli; Ahmad Salahuddin M Azizan; Faridah Che Husain; Noor Hafizah Mohd Haridi, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This systematic literature review examines the ethical frameworks surrounding the adoption of artificial intelligence (AI) in the professional practices of higher education lecturers. As AI becomes increasingly prevalent in academia, it presents ethical challenges, including concerns about academic integrity, data privacy, algorithmic fairness, and its responsible implementation in teaching and research. These issues underscore the need for robust ethical guidelines to support educators in navigating the complexities of AI integration. The study aims to analyze existing ethical frameworks for AI adoption in higher education, identify key challenges and opportunities in AI integration, and develop comprehensive guidelines for responsible AI implementation. The methodology followed the PRISMA guidelines, employing qualitative systematic review through content analysis and thematic synthesis. Advanced searches in Scopus and Web of Science databases identified 34 primary studies that met the inclusion criteria, focusing on peer-reviewed articles published in 2024 about AI ethics in higher education. The findings were divided into three themes: (1) Ethical Concerns and Academic Integrity, (2) Pedagogical Strategies and Educational Impact and (3) Policies and Frameworks for AI Integration. Results indicate a growing need for standardized ethical frameworks, with 85% of studies emphasizing the importance of balancing innovation with ethical considerations. Conclusions highlight the necessity for adaptable and inclusive frameworks that prioritize accountability, transparency, and equity in AI use within higher education.